QbD-driven development of intranasal lipid nanoparticles for depression treatment - Vitorino, Carla (2020)
Depression is a life-threatening psychiatric disorder and a multifactorial global public health concern. Current pharmacological treatments present limited efficacy, and are associated with several harmful side effects and development of pharmacoresistance mechanisms. Developing more effective therapeutic options is therefore a priority. This work aims at efficiently designing an antidepressant therapeutic surrogate relying on a dual strategy supported on lipid nanoparticles and intranasal delivery. For that purpose, the formulation was comprehensively optimized following a quality by design perspective. Critical quality attributes (CQAs) ranged from physicochemical to intranasal performance features. The optimized formulation was administered to mice in order to assess the antidepressive and anxiolytic effects by applying the forced swimming and marble-burying tests, respectively. A cross-analysis of the predictive models established for the set of 12 CQAs elicited the formulation containing similar proportion of solid and liquid lipids and lower surfactant concentration as the optimal one. Despite increasing the liquid lipid amount yielded smaller and more homogeneous particle size, and higher release rate, nanostructured lipid carriers (NLCs) provided an earlier and superior pig nasal mucosa permeability than nanoemulsions, along with better stability and cytotoxic profiles. Importantly, the intranasal delivery of the optimal lipid nanoparticle formulation reduced both depressive and anxiety-like behaviors, which positions these intranasal nanosystems in line with the hypothesis of provisioning timely and better acting antidepressant therapies.